ANALISIS FAKTOR-FAKTOR PENYEBAB KESULITAN BELAJAR SISWA PADA MATA PELAJARAN AKUNTANSI - Fitri Nurlaili; Nely Hartika; Triana Sri Handayani (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2020)
This study aimed to: (1) to find out Internal factors that influence student learning difficulties in accounting subjects (2) To find out any external factors that influence student learning difficulties in accounting subjects ;(3) To find out dominant factors influence the causes of learning difficulties in accounting subjects. This research method was quantitative research. The population in this study were all students of class XI Accounting in the odd semester of state vocational high school (SMKN) in Serang City. The validity of the questionnaire instrument was performed by item analysis used the Product Moment correlation formula and the reliability test used the Cronbach’s Alpha formula. The data analysis technique used factorial analysis Confirmatory factor analysis model. The results of this study indicated that: the biggest internal factor that causes the learning difficulties for learners was (1) a physical factor with eigenvalue of 3.735 and a variance value of 19,659% (2) the biggest external factor that caused the learning difficulties were family factors with an eigenvalue of 3.735 and a variance value of 19.6%.